Human Centric Technology and Service in Smart Space HumanCom 2012 - Park, James J. (Jong Hyuk).; Jin, Qun.; Sang-soo Yeo, Martin; Hu, Bin.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
The theme of HumanCom is focused on the various aspects of human-centric computing for advances in computer science and its applications and provides an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of human-centric computing. In addition, the conference will publish high quality papers which are closely related to the various theories and practical applications in human-centric computing. Furthermore, we expect that the conference and its publications will be a trigger for further related research and technology improvements in this important subject.
Human-computer interaction and User-centered Design -- Social computing and social intelligence -- Ubiquitous computing and mobile systems -- Gaming -- Computer-assisted Learning and Cognition -- Privacy, Security and trust management -- Human-centered Evaluation -- Information Visualization and Visual Analytics -- Embedded Systems and Software -- Dependable, Reliable and Autonomic Computing -- Embedded Smart Agents -- Context awareness and inference -- Multi modal interaction design -- U/E-Healthcare Services -- Virtual Humans & Virtual Worlds -- Wearables sensors and actuators -- Grid and Cloud Computing -- Mobile Device and Smartphone -- Smart Learning Services -- Social Media and Collaborative Systems -- Data Mining for Human-Com -- Information Services for an Aging Society -- Recommender Systems for Human-Com -- Speech in Interactive Computing -- Virtual Reality Software and Technology.
Keywords: Engineering; User interfaces (Computer systems).; Computer graphics; Computational intelligence; Electrical engineering; Engineering; Communications Engineering, Networks; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Computational Intelligence; Electronic books